Development of Swallowing Function in Infants with Oral Feeding Difficulties. (3rd February 2020) - Han, Changhun; Shin, Jaeho; Jeon, Ga Won
Abstract : Background . Discharge of preterm infants is often delayed because of their oral feeding difficulties. Independent oral feeding is the last obstacle to pass after managing acute and chronic morbidities. We conducted this study to determine the prevalence, characteristics, and risk factors of swallowing dysfunction and suggest proper interventions to reduce aspiration and chronic lung injury. Methods . Infants admitted to the neonatal intensive care unit (January 2016 to December 2018) who were performed modified barium swallow study due to oral feeding difficulties were enrolled. Modified barium swallow study was done ≥ postmenstrual age 37 weeks to limit radiation exposure. Clinical data were collected retrospectively. Swallowing dysfunction was defined as inadequate epiglottic closure, laryngeal penetration, or tracheal aspiration according to result of the modified barium swallow study. Results . Among a total of 54 infants enrolled, nine (16.7%) were term infants, 13 (24.1%) were late preterm infants (gestational age, 34-36 weeks), and 32 (59.3%) were early preterm infants (gestational age < 34 weeks). Gestational age and birth weight were smaller in infants with swallowing dysfunction. Total duration of mechanical ventilation and duration of invasive ventilation were longer in infants with swallowing dysfunction. The risk of swallowing dysfunction increased by 11.2 times for infants with gestational age < 29 weeks compared to infants with gestational age ≥ 29 weeks. Swallowing dysfunction was improved in most infants after they became matured. They showed different time and rate of maturation with the help of rehabilitation through swallow therapy and dietary modification with thickened formula. Conclusion . Preterm infants with gestational age < 29 weeks or with longer ventilation duration are at a higher risk of aspiration. Rehabilitation of swallow therapy and dietary modification with thickened formula can be helpful interventions to prevent aspiration and chronic lung injury and reassure parents until independent oral feeding is possible.